Using Personal Values to Understand the Motivational Basis of Amity Goal Orientation - Levontin, Liat; Bardi, Anat (Frontiers in Psychology, 2019)
Values are broad motivations that can serve as the basis for goals. We propose that values can be used to understand the motivational basis of amity goal orientation, a prosocial goal orientation within achievement situations. We offer theory and empirical evidence relating personal values to amity goal orientation and other achievement goal orientations. Specifically, the results of three studies and a mini meta-analysis suggest that the prosocial value of benevolence is positively related to amity goal orientation and can be interpreted as the motivational basis of amity goal orientation. Furthermore, power values are positively related to performance-approach goal orientation; self-direction values are positively related to mastery goal orientation, and security values are positively related to performance-avoidance goal orientation. These findings can explain the pattern of correlations previously found among achievement goal orientations, and open up the potential for new research on amity goal orientation as well as other value-based achievement goal orientations.